Assessment of Risk for Seclusion Among Forensic Inpatients: Validation and Modification of the Risk of Administrative Segregation Tool (RAST). (June 2019) - Hilton, N. Zoe; Ham, Elke; Seto, Michael C.
Seclusion is used in psychiatric care to protect patients and staff or to manage aggression but may have adverse effects. The ability to identify at-risk patients could help reduce seclusion. This study tested the Risk of Administrative Segregation Tool's (RAST) ability to predict any seclusions among 229 male forensic inpatients followed for up to 1 year of hospitalization, and days spent secluded, controlling for length of stay. RAST scores were lower than in correctional samples. The RAST did not predict seclusions in Year 1, but modification of three items to fit the forensic population (RAST-F) offered a small improvement. Among 62 patients hospitalized for more than 1 year, the RAST significantly predicted seclusions in Year 2, and the modifications improved prediction. The present modest findings support the RAST's potential to help identify patients most in need of clinical efforts to avert seclusion. Replication in larger samples, including female patients, is needed.